Analisis Kinerja Unit Kegiatan Mahasiswa Dalam Pengembangan Sumber Daya Manusia: Studi Kasus Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa - Muhamad Ikhwan Bagus; Aprilla Fortuna; Muhammad Ilham; Megi Hedian Nura (PAKAR Pendidikan, 2023)
Changes in behavior in the new normal era that have occurred since the pandemic at the end of 2019 until now have caused changes to occur from all orders of life, one of which is the world of education felt by students. All online activities have become the main material that must be adapted by students both in learning and activities or student organizations, but with the easing of health protocols, activities that were previously online beginning to gradually be transferred to offline, although not all of them. The Center for Scientific Development and Student Research of Padang State University is a student activity unit engaged in research, science, and community service which is one of the units that have changed the work strategy of the management in achieving the vision and mission and common goals in the organization. Since the easing of health protocol regulations, this organization has slowly begun to change the format of its activities that were previously full online to blended, namely some are online and some are offline. Therefore, it is necessary to research the performance of administrators from the perspective of members who serve in the new normal era in pandemic conditions like now. The type of research used is quantitative descriptive research with a Likert scale approach. The data type used is primary data. The study was conducted in the middle of July to early August 2022. The results showed that after researching the performance and level of satisfaction, it was known that the overall performance of the management was by expectations and had a positive influence on the level of member satisfaction.